Assessment of the population demand for high-cost medical interventions: are there any reliable criteria? - I. V. Samorodskaya (Кардиоваскулярная терапия и профилактика)
The paper discussed the causes of the substantial geographical discrepancies in the rates of cardiosurgery interventions, based on the secondary analysis of international data. The impact of these differences on mortality levels is assessed. The methods for population demand assessment are reviewed, with the focus on the intervention rates across the countries and the “number needed to treat” parameter.